Why size matters: the interactive influences of tree diameter distribution and sap flow parameters on upscaled transpiration. (13th October 2017) - Berry, Z Carter; Looker, Nathaniel; Holwerda, Friso; Gómez Aguilar, León Rodrigo; Ortiz Colin, Perla; González Martínez, Teresa; Asbjornsen, Heidi
Abstract: In stands with a broad range of diameters, a small number of very large trees can disproportionately influence stand basal area and transpiration ( E t ). Sap flow-based E t estimates may be particularly sensitive to large trees due to nonlinear relationships between tree-level water use ( Q ) and tree diameter at breast height (DBH). Because Q is typically predicted on the basis of DBH and sap flow rates measured in a subset of trees and then summed to obtain E t, we assessed the relative importance of DBH and sap flow variables (sap velocity, V s, and sapwood depth, R s ) in determining the magnitude of E t and its dependence on large trees in a tropical montane forest ecosystem. Specifically, we developed a data-driven simulation framework to vary the relationship between DBH and V s and stand DBH distribution and then calculate Q, E t and the proportion of E t contributed by the largest tree in each stand. Our results demonstrate that variation in how R s is determined in the largest trees can alter estimates up to 26% of E t while variation in how V s is determined can vary results by up to 132%. Taken together, these results highlight a great need to expand our understanding of water transport in large trees as this hinders our ability to predict water fluxes accurately from stand to catchment scales.